Mercado de formación y disponibilidad de profesionales de ciencias de la salud en el Perú - Jiménez, M. Michelle; Mantilla, Eduardo; Huayanay-Espinoza, Carlos A.; Gil, Karina; García, Hernán; Miranda, J. Jaime (Instituto Nacional de Salud, 2015)
Objectives. To describe the availability and demand of professional training programs for eight health science professions in Peru. Study the profiles of the physicians, nurses and midwives that these programs train and their competencies to work at the primary health care level. Materials and methods. Cross-sectional study using data on the volume of applicants, students and graduates of these eight professional training programs during the period 2007 - 2011. In addition, the curricula of professional training programs for physicians, nurses and midwives from public and private universities were analyzed, along with competency profiles developed by Professional Colleges and the Ministry of Health. Results. Admission rates in public and private universities vary by program: 4% and 28% respectively for medical schools, and 18% and 90% for nursing. Graduation rates were estimated at approximately 43% and 53% of students entering medicine and nursing training programs respectively. Contrasting the profiles of recently graduated professionals in medicine, nursing and midwifery, with the skills required by the Ministry of Health for professionals working in primary care the first level of care, indicate that these recently graduated professionals are not necessarily or specifically trained to work in primary care. Conclusions. Demand for professional training in health sciences exists and its supply is met predominantly by private universities. Competency profiles developed by the MOH for the basic professional health team in primary care shows a clear disconnect regarding the current supply of trained professionals.

Objetivos. Describir el mercado de formación y la disponibilidad de profesionales de ocho carreras de ciencias de la salud en Perú. Además, examinar los perfiles de los médicos, enfermeros y obstetras que se forman y sus competencias para trabajar en el primer nivel de atención. Materiales y métodos. Estudio transversal utilizando datos de volumen de postulantes, ingresantes y graduados de ocho profesiones durante el periodo de 2007–2011. También se analizaron los planes de estudio de programas de formación de médicos, enfermeros y obstetras de universidades públicas y privadas, y los perfiles de competencias elaborados por los colegios profesionales y el Ministerio de Salud (MINSA). Resultados. Las tasas de ingreso en universidades públicas y privadas varían según la carrera: 4 y 28% respectivamente para Medicina Humana, y 18 y 90% para Enfermería. Además, se estima que se gradúan aproximadamente 43 y 53% de los estudiantes que ingresan a Medicina y Enfermería, respectivamente. El análisis del perfil de los profesionales recientemente graduados en Medicina, Enfermería y Obstetricia, al ser contrastados con el perfil de competencias priorizadas para los profesionales que laboran en el primer nivel de atención elaborado por el MINSA, indican que no están necesariamente ni específicamente formados para trabajar en este nivel de atención. Conclusiones. Existe demanda de formación para profesionales de ciencias de la salud y predomina la oferta por parte de universidades privadas. Los perfiles de competencias desarrollados por el MINSA muestran un claro divorcio con respecto a la oferta actual de profesionales formados.
Keywords: Training; Capacity building; Capacitación; Delivery of health care; Creación de capacidad; Developing countries; Prestación de atención de salud; Países en desarrollo; Health manpower; Recursos humanos en salud; https://purl.org/pe-repo/ocde/ford#3.03.02